The Demand for Children in Farm Households - Rosenzweig, Mark R. (Journal of Political Economy, 1977)
A multiperiod household model of fertility behavior applicable to rural-agricultural settings in which the pecuniary as well as the psychic returns from children are significant is formulated. Implications regarding the effects of variables associated with the market for agricultural labor on the demand for farm children, including technical change, agricultural wage rates, farm value, and nonfarm employment opportunities, derived from the model are tested on U.S. aggregate data covering the period 1939-60. The empirical results obtained appear to support the theoretical model and suggest the importance of the reduction in the value of children as productive assets in agriculture as a factor in the postwar decline in the U.S. farm birth rate.